Carbon‐14 bomb pulse dating shows that tendinopathy is preceded by years of abnormally high collagen turnover. Issue 9 (23rd March 2018) - Heinemeier, Katja Maria; Schjerling, Peter; Øhlenschlæger, Tommy F.; Eismark, Christian; Olsen, Jesper; Kjær, Michael
ABSTRACT: Tendons are essential weight‐bearing structures that are often affected by tendinopathy, which leads to pain and impaired mobility. In healthy Achilles tendons, no significant renewal of the weight‐bearing collagen matrix seems to occur during adult life, but tendinopathy may lead to increased turnover. The carbon‐14 ([ 14 C]) bomb pulse method was used to measure lifelong replacement rates of collagen in tendinopathic and healthy Achilles tendons (tendinopathic: n = 25, born 1937–1972. Healthy: n = 10, born 1929–1966). As expected, the healthy tendon collagen had not been replaced during adulthood, but in tendinopathic tendon, a substantial renewal had occurred. Modeling of the [ 14 C] data suggested that one half of the collagen in tendinopathic matrix had undergone continuous slow turnover for years before the presentation of symptoms. This finding allows for a new concept in tendon pathogenesis because it suggests that either the symptoms of tendinopathy represent a late phase of a very prolonged disease process, or an abnormally high collagen exchange could be a risk factor for tendon disorders rather than being a result of disease.—Heinemeier, K.M., Schjerling, P., Øhlenschlæger, T. F., Eismark, C., Olsen, J., Kjær, M. Carbon‐14 bomb pulse dating shows that tendinopathy is preceded by years of abnormally high collagen turnover. FASEB J. 32, 4763–4775 (2018). www.fasebj.org